THE CONCEPT OF ALIENATION IN THE EARLY WORKS OF KARLMARX - Oliver Christ (European Scientific Journal, ESJ, 2015)
The main analysis of alienated labor was developed by Karl Marx in his early work Economic and Philosophical Manuscripts from 1844. Marx differentiates between four dimensions of alienated labor in capitalist modes of production: The alienation of individuals (workers) from the product, from economic activity, from their species-being, and the alienation of individuals from one another. Together with the description of four forms of alienation, Marx provides approaches for an anthropological definition of humans, who can be summarized in the conception of humans as ‘representational species-beings’. According to Marx, the individual is a creature who acts in relationship to his own species and to human society. Under the conditions of private ownership and exchange, the individual alienates himself from his species-being and his fellows, whom he views solely as a means of achieving personal objectives. Following the analysis of alienated labor, Karl Marx provides in his early works initial indications of his ideas on a superseded alienation. In the case of human modes of production, where private ownership is positively superseded, Marx lists four different forms of affirmation, which are conceived of in the sense of recognition relationships and also relate to the anthropological definition of humans as ‘representational species-beings’.